Dampak Subsidi Energi terhadap Kesejahteraan Masyarakat Miskin di Indonesia - Adelia Gusfira; Hasanatun Fitri; Ahmad Wahyudi zein (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Energy subsidy policy has become one of the key strategies of the Indonesian government in its efforts to improve public welfare, particularly for low-income groups. By subsidizing fuel (BBM), 3-kg LPG, and electricity tariffs, the government aims to stabilize energy prices to make them more affordable for the poor. However, the effectiveness of this policy in achieving social welfare goals remains debatable, especially regarding the accuracy of subsidy distribution. This study aims to analyze the impact of energy subsidies on the welfare of poor households in Indonesia using both qualitative and quantitative approaches based on secondary data from BPS, the Ministry of Finance, and reports from international institutions such as the World Bank and the IMF. The analysis shows that although energy subsidies provide direct benefits by reducing the household expenses of the poor, a significant portion of the subsidies is actually enjoyed by middle- and high-income households. This unequal distribution reduces the effectiveness of subsidies as a tool for promoting welfare equity. Therefore, reform of energy subsidy policies is needed to improve targeting accuracy, such as by converting subsidies into direct cash transfers based on social data. These findings offer important implications for the formulation of more efficient and equitable fiscal and social protection policies in the future.